ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) SEBAGAI SUMBER PENDAPATAN ASLI DAERAH KABUPATEN MINAHASA, KABUPATEN MINAHASA UTARA, DAN KOTA MANADO - Chichi, Juriko; Nangoi, Grace B.; Pangerapan, Sonny (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
The collection of land and building tax is based on law no. 12 year 1985. Land and building tax for rural and urban district is a new potential income for own-source revenue. The purpose of this research is to find out the effectiveness and contribution of land and building tax for rural and urban district as a own-source revenue for Minahasa District, Northern Minahasa District, and Manado City. This research uses the qualitative descriptive method. Method that used for data collection in this research is direct interview with the parties appointed by the Local Revenue Office in each district. Result of the research shows that the effectiveness of land and building tax for rural and urban district for Northern Minahasa District is 103,26% (very effective), Manado City is 95,52% (effective), and Minahasa District is 69,78% (less effective). The contributions of land and building tax for rural and urban district for own-source revenue for Northern Minahasa District is 17,27% (less), Manado City is 9,46% (very less), and Minahasa District is 5,29% (very less).Keyword : PBB-P2, income, effectiveness, contributions